Polymorphism of ITS4 Gene of Candida guilliermondii - Wafaa K. Al-mansour (Journal of Global Pharma Technology, 2018)
The aim of this study is investigate the polymorphisms of Candida guilliermondii based on ITS4 gene sequencing. To achieve this goal, samples were collected from patients with dermal infection symptoms, were applied for microbiological analysis using SDA media DNA was isolated from Candida guilliermondii and the ITS4 gene were amplified by using specific primer, then sequencing of nucleic acid of genes was performed by machine is AB13730XL, Applied Biosystem, Macro gen company, the DNA sequencing results of flank sense of ITS4 gene from 5 strains of Candida guilliermondii was found to be compatible 99% and score 1517 and expect 0.0 of the ITS4 gene of Candida guilliermondii strain BO418 from the Gene Bank, The expected substitution were found after the analysis of the sequences there were 5 Transversion and one transition in the 5 Candida guilliermondii with Sequence ID emb|AJ3tf10144.1| location at range of nucleotide from 5128 to 5408, compared with data obtained from Gene Bank, these finding lead to conclusion, our assay allows rapid detection of Polymorphism in Candida guilliermondii.Key words: Candida guilliermondii, ITS4 gene, Polymorphism, and Sequencing.